Preeclampsia y eclampsia como factores de riesgo para transtornos del espectro autista - Quiróz Aldave, Juan Eduardo (2017)
It was realized an analytic, case control study in 111 children affected with Autism Spectrum Disorder (ASD) and 333 children without this pathology who consulted in Neuropediatrics in Belen Hospital of Trujillo between January 2010 and march 2015. The objective was to determine the association between preeclampsy/eclampsy and the development of ASD. It was found in 40,54% of the children with ASD the antecedent of preeclampsy/eclampsy in their mothers, while it was present in 4,20% of the children without ASD. It was found association between preeclampsy/eclampsy and the development of Autism Spectrum Disorders (OR = 15,54; ℎ = 9,75; CI 95% = 8,07 – 29,94; p<0,05). It was concluded that preeclampsy/eclampsy is a risk factor for the development of autism spectrum disorders